A strategic learner for a new society - Bernardo Gargallo López (Ediciones Universidad de Salamanca, 2012)
<!--[if gte mso 9]> Normal.dotm 0 0 1 166 949 Universidad de Salamanca 7 1 1165 12.0 <![endif]--><!--[if gte mso 9]> 0 false 18 pt 18 pt 0 0 false false false <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> <!--StartFragment--> <span style="font-size: 12.0pt; line-height: 115%; font-family: ";Times New Roman";; mso-fareast-font-family: Calibri; mso-bidi-font-family: ";Times New Roman";; color: black; background: white; mso-ansi-language: EN-US;" lang="EN-US">New times require new learners. <span style="font-size: 12.0pt; line-height: 115%; font-family: ";Times New Roman";; mso-fareast-font-family: Calibri; mso-bidi-font-family: ";Times New Roman";; color: black; background: white; mso-ansi-language: EN-US;" lang="EN-US">Developing<span style="font-size: 12.0pt; line-height: 115%; font-family: ";Times New Roman";; mso-fareast-font-family: Calibri; mso-bidi-font-family: ";Times New Roman";; color: black; background: white; mso-ansi-language: EN-US;" lang="EN-US"> <span style="font-size: 12.0pt; line-height: 115%; font-family: ";Times New Roman";; mso-fareast-font-family: Calibri; mso-bidi-font-family: ";Times New Roman";; color: black; background: white; mso-ansi-language: EN-US;" lang="EN-US">new attitudes and skills for learning is necessary <span style="font-size: 12.0pt; line-height: 115%; font-family: ";Times New Roman";; mso-fareast-font-family: Calibri; mso-bidi-font-family: ";Times New Roman";; color: black; background: white; mso-ansi-language: EN-US;" lang="EN-US">in a school<span style="font-size: 12.0pt; line-height: 115%; font-family: ";Times New Roman";; mso-fareast-font-family: Calibri; mso-bidi-font-family: ";Times New Roman";; color: black; background: white; mso-ansi-language: EN-US;" lang="EN-US"> immersed in the information society, which we want to become the knowledge society.<span style="font-size: 12.0pt; line-height: 115%; font-family: ";Times New Roman";; mso-fareast-font-family: Calibri; mso-bidi-font-family: ";Times New Roman";; color: black; background: white; mso-ansi-language: EN-US;" lang="EN-US"> <span style="font-size: 12.0pt; line-height: 115%; font-family: ";Times New Roman";; mso-fareast-font-family: Calibri; mso-bidi-font-family: ";Times New Roman";; color: black; mso-ansi-language: EN-US;" lang="EN-US">The students must learn to develop their autonomy and responsibility in an open world where there are a lot of information and stimuli. In this context, it's necessary the student to become a "strategic learner", an autonomous person who wants to learn to grow for himself and for other people, with reference to values; someone who learns to mobilize, observe, assess, plan and control their own learning processes. We're talking about self-regulated learning, about "learning to learn". And, although it's true that the school has lost its key role in the transmission of information, it is also true that the school becomes a privileged place to teach learning to learn. The self-regulation, the critical thinking, the civic commitment, etc. have to settle in the school to continue growing, and they can be taught and must be taught from an early age. In this work we enclose some clues for the development of strategic learning in the educational system. <!--EndFragment-->